Assessing the Influence of Influencer Leadership, Digital Transformation and Social Climate on Improving Teacher Achievement in Building Excellent Madrasahs - Suci Hidayati; Munirul Abidin; Andika Harianto Subakti; Aini Rizqoh (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. Achievement in the world of education is identical to the achievement of student learning outcomes in academic or non-academic fields. The focus of education tends to be on output. It turns out that outstanding teachers are able to become an important element as producers of quality generations who are competitive at the global level and successful in their future lives. Purpose. The focus of the study aims to assess how much influence influencer leadership, digital transformation and social climate have on improving teacher achievement in building superior madrasas. Method. This study uses a descriptive quantitative approach with data analysis techniques using Smart-PLS to measure variables that influence and influence each other. The number of respondents in the study was 124 private madrasa teachers in Malang Regency with a liket scale measurement of 1-5. Analysis of the Cronbach's alpha value which is overall greater than 0.7 can explain the existence of a construct that is internally consistent and reliable in testing. Results. The results of the study showed that: (1) There is a significant influence between influencer leadership and improving teacher achievement; (2) there is a significant influence between digital transformation and improving teacher achievement and (3) there is no significant influence between social climate and improving teacher achievement. Conclusion. Predictively, researchers see that psychological factors in the form of self-efficacy have a greater influence than social climate in terms of improving teacher achievement. The dependent variables in this study have a significant influence of 54.2%. to the independent variable.